2018
DOI: 10.1111/jfpp.13602
|View full text |Cite
|
Sign up to set email alerts
|

Study on the effect of pilot scale roasting conditions on the physicochemical and functional properties of maize flour (Cv.Bio 22027)

Abstract: Maize kernels were subjected to pilot scale roasting treatment for different time (10–35 min) and temperature (170–200 °C) combinations using a full factorial design. The changes in physicochemical (moisture content, browning index, hardness, bulk density, degree of gelatinization), and functional properties (in vitro protein digestibility [IVPD] index, water/oil absorption capacity [OAC]) were measured as responses which were fitted to quadratic models. The optimized conditions obtained by roasting for 25 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
3
2
0
Order By: Relevance
“…Moreover, the physical properties of seeds as a function of moisture content plays a vital role in implicating its effect on the physicochemical parameters and functional attributes of the powder so obtained. A similar study was reported by Raigar and Mishra (). The moisture content of seeds also affects the yield and particle size distribution of the obtained powder, which is being justified by Raigar et al, ().…”
Section: Introductionsupporting
confidence: 87%
“…Moreover, the physical properties of seeds as a function of moisture content plays a vital role in implicating its effect on the physicochemical parameters and functional attributes of the powder so obtained. A similar study was reported by Raigar and Mishra (). The moisture content of seeds also affects the yield and particle size distribution of the obtained powder, which is being justified by Raigar et al, ().…”
Section: Introductionsupporting
confidence: 87%
“…The carbohydrate content of all samples was high, with CF presenting a significantly ( p < 0.05) higher content (80.40 ± 0.29 g/100 g) than FF (70.55 ± 0.24 g/100 g). The lower carbohydrate content of the FF, which supports previous research [ 18 ], can likely be attributed to the Maillard reaction [ 15 ]. The energy content of the samples was considerable, with HF having significantly ( p < 0.05) the highest energetic value (377.60 ± 1.00 kcal/100 g) among all flour samples.…”
Section: Resultssupporting
confidence: 89%
“…The crude protein content of our samples is in accordance with existing literature [ 12 ], ranging from 6.08 ± 0.11 to 10.86 ± 0.36 g/100 g. Furniko flour (FF) exhibited the highest protein content among all tested samples, a statistically significant difference ( p < 0.05). In contrast to Oboh et al [ 5 ], this observation supports the conclusion that roasting can enhance protein content [ 13 , 14 ], possibly due to heat-induced protein denaturation and moisture loss [ 15 ]. A significant variation was observed in the fat content of the flour samples ( p < 0.05).…”
Section: Resultssupporting
confidence: 77%
“…Table 3 shows the setting restrictions and predicted values with individual desirability of the response parameters for optimization. An individual desirability of 1 indicates the expected response to be on target (Raigar & Mishra, 2018). All the geometric means used by all the individual desirability are combined to generate the composite desirability.…”
Section: Optimization and Validation Of Roasting Conditionsmentioning
confidence: 99%